Tanggung Jawab Sosial Perusahaan (CSR) Dunia Usaha dalam Percepatan Penurunan Stunting: Program Dapur Sehat Atasi Stunting (DASHAT) di Kota Cilegon - Luki Oka Prastio; Kheria Yulia Ningrum; Ika Arinia Indriyany (Nakhoda: Jurnal Ilmu Pemerintahan, 2026)
This research examines the involvement of the business sector in accelerating stunting reduction in Cilegon City in 2024. Presidential Regulation of the Republic of Indonesia No. 72 of 2021 on the Acceleration of Stunting Reduction, issued by President Joko Widodo, stipulates that several parties are related to the acceleration of stunting reduction, one of which is the business sector. The active involvement of the business sector is needed to maintain the five pillars of the national strategy. Cilegon City, one of the regions implementing the Acceleration of Stunting Reduction, also actively involves the business sector in stunting reduction activities, one of which is the Healthy Kitchen to Overcome Stunting (DASHAT) program. Using a qualitative method and a case study approach, this research dissects the contribution of the business sector to stunting reduction policy in Cilegon City. Drawing on the concept of corporate social responsibility (CSR), the findings indicate that implementation of the DASHAT program in Cilegon City still faces several obstacles, such as the government’s limited budget. On this basis, the Cilegon City Government collaborates with the business sector to remain committed to reducing stunting despite the limited budget. The involvement of the business sector can be seen in its role as a facilitator that provides funding. In 2024, 39 companies contributed to stunting reduction in Cilegon City, one of which was PT Latinusa Tbk. This research recommends that the acceleration of stunting reduction requires commitment from all stakeholders, including the involvement of the business sector through CSR programs.